2020
DOI: 10.1016/j.psychres.2020.113138
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of symptoms of anxiety and depression and mental wellbeing associated with COVID-19: a cross-sectional study of UK-based respondents

Abstract: Background: The aim was to assess the impact of COVID-19 self-isolation/social distancing on mental health, and potential correlates, among a sample of the UK population. Methods: A cross-sectional study. Mental health was measured using the Beck Anxiety and Depression Inventory. Mental wellbeing was measured using The Short Warwick-Edinburgh Mental Well-being Scale. Data collected on predictors included sex, age, marital status, employment, annual income, region, current smoking, current alcohol consumption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
338
4
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 360 publications
(415 citation statements)
references
References 25 publications
51
338
4
22
Order By: Relevance
“…This nding coincides with our study as it raised almost similar levels (moderate to very high level) of psychological distress (62.6%) among the study participants. A study from the UK showed that the prevalence of poor mental health was 37% amongst participants who were in isolation or maintaining social distancing, where poor mental health was de ned as having moderate to severe depressive symptoms and anxiety [26]. Similarly, the Australian Bureau of Statistics had been collecting COVID-19 impact survey data fortnightly involving a representative sample of over 1,000 adults across Australia, and ndings indicated twice as many adults experiencing anxiety, nervousness and restlessness compared to pre-COVID surveillance data [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This nding coincides with our study as it raised almost similar levels (moderate to very high level) of psychological distress (62.6%) among the study participants. A study from the UK showed that the prevalence of poor mental health was 37% amongst participants who were in isolation or maintaining social distancing, where poor mental health was de ned as having moderate to severe depressive symptoms and anxiety [26]. Similarly, the Australian Bureau of Statistics had been collecting COVID-19 impact survey data fortnightly involving a representative sample of over 1,000 adults across Australia, and ndings indicated twice as many adults experiencing anxiety, nervousness and restlessness compared to pre-COVID surveillance data [27].…”
Section: Discussionmentioning
confidence: 99%
“…All items were scored, and the total score categorised into low (score 10-15), moderate (score [16][17][18][19][20][21], high (score 22-29) and very high (score 30-50). FCV-19S has seven items and the response to each item was also measured using a 5-point Likert scale (strongly disagree, somewhat disagree, neither agree nor disagree, somewhat agree, strongly agree), with scores categorised into low (score 7-21) and high (score [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. BRCS has four items and responses were collected again using a 5-point Likert scale (does not describe me at all, does not describe me, neutral, describes me, describes me very well), with scores similarly categorised into low (score 4-13), medium (score 14-16) and high (score 17-20) resilient copers.…”
Section: Study Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…When asked retrospectively, 25.4% of the Chinese general public reported feeling that their mental health had deteriorated since the pandemic began [ 5 ]. Elevated mental health problems are also present among adults in the United Kingdom [ 8 ], Spanish university students and staff [ 9 ] and adults in the United States, where 43.3% reported high levels of depression and 45.4% reported high levels of anxiety [ 10 ]. Similarly, in Denmark, the general population’s psychological well-being was lower during the COVID-19 pandemic, compared to data collected in 2016 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These potentially detrimental effects of information seeking could perhaps be due to having constant access to information about the pandemic through the Internet, which could have harmful effects [ 4 , 32 ], as well as traditional media not being updated throughout the day with multiple stories on how the disease manifests. The potential harm of information seeking can also be seen among young adults, who are more likely to use the Internet to access information and are more susceptible to psychological symptoms during COVID-19 [ 2 , 4 , 8 , 13 , 32 ].…”
Section: Introductionmentioning
confidence: 99%